15. STUDY ON THE NEED FOR KIDNEY TRANSPLANTATION AND PATIENTS ON KIDNEY TRANSPLAT WAITING LIST IN LAO CAI PROVINE 2023 (Tạp chí Y học Cộng đồng, 2023)
Objectives: This study aims to determine the need for kidney transplantation and patients on kidney transplant waiting list in Lao Cai provine 2023. Methods: A cross-sectional descriptive study was conducted on all patients undergoing hemodialysis at 4 hospitals in Lao Cai province from October 2022 to March 2023. Results: Lao Cai province has 4 hemodialysis units with a need for kidney transplants in the province of 214 people, mainly at the provincial general hospital, with an average age of 50, men making up the majority with more than 60% and the majority of patients have been on dialysis for less than 5 years. 74% of patients in need of a kidney transplant were on the waitlist. Initially, it was determined that Lao Cai has 159 patients waiting for a kidney transplant with an average age of 43 and 61.6% have been on dialysis for less than 5 years. Among these patients, the majority of patients with blood type O account for more than 40%, and the rates of hepatitis B and C are 13.7% and 17.8%, respectively. Chronic glomerulonephritis is the main cause, accounting for more than 80% of patients requiring hemodialysis. Conclusions: In 2023, Lao Cai has 214 patients in need of kidney transplant. 159 patients waiting for a kidney transplant are concentrated mainly at the provincial general hospital with an average age of 43, most of whom have been on dialysis for less than 5 years. The main cause of dialysis is chronic glomerulonephritis.
Keywords: Kidney transplant need, kidney transplant waiting list.